Belize : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2004)
An illegal parallel market for foreign exchange is prevalent in Belize. Its emergence and continued existence is attributed to the pervasive exchange controls, attempts to avoid banking fees, as well as the prevalence of cash transactions in the tourist sector. Overall, the financial system appears sound, the banking system is well capitalized, and the insurance sector has been able to pass most of the risks offshore through reinsurance. The supervisory and regulatory framework for commercial banks appears sound, but there is scope for improvement.